Pengaruh Paparan Asap Rokok terhadap Kejadian ISPA pada Anak di Puskesmas Tepeleo, Kabupaten Halmahera Tengah - Widia Mahbub; Widia Shofa Ilmiah (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Acute respiratory infections remain one of the leading causes of morbidity among children under five, particularly in areas where environmental risk factors such as household cigarette smoke persist. This study aimed to examine the relationship between household cigarette smoke exposure and the incidence of respiratory infections in children. A cross-sectional quantitative design was used, involving 30 children aged 0–5 years who visited Tepeleo Health Center, Central Halmahera, between January and March 2025. Data were collected using structured questionnaires and analyzed using contingency coefficient testing to determine the strength of association between smoke exposure and infection occurrence. The results show that 40% of children live in households where smoking occurs indoors, and among these, most present with symptoms of respiratory illness, including influenza, pharyngitis, and the common cold. The analysis reveals a strong association between exposure to cigarette smoke and the incidence of respiratory infections, with a contingency coefficient value of 0.651 and a p-value of 0.000. Children in smoking households tend to develop infections more frequently than those in smoke-free environments. The findings confirm that cigarette smoke is a prominent preventable factor contributing to poor respiratory health in children. The study highlights the urgent need for family-based education and the implementation of smoke-free home policies as practical measures to reduce respiratory disease risk. Promoting awareness and behavior change among caregivers plays a vital role in ensuring a healthy indoor environment for child development.